ANALISIS PENDAPATAN USAHATANI BERDASARKAN WAKTU TANAM DAN KARAKTERISTIK PEMASARAN UBI KAYU DI KECAMATAN BUMI NABUNG KABUPATEN LAMPUNG TENGAH - Dea Adelia; Raden Hanung Ismono; Ani Suryani (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
The research was designed to determine the best planting month, the size of farm income, the value of revenue/cost ratio (R/C), the correlation between R/C and the price as well as production of cassava, and the marketing efficiency. This research was conducted in district Bumi Nabung Lampung Tengah Regency.Respondents were 60 cassava farmers in District Bumi Nabung. The R/C value was determined from the farming income method, the correlation by Pearson Correlation test method, and the marketing efficiency by SCP (market Structure, market Conduct, market Performance) method. Data were analyzed in the manner of descriptive qualitatively and quantitatively. The results indicated that the best planting months was either the farmer planted in June or July with the R/C values of 3.49 and 3.85. The correlation between R/C and the production was inversely proportional and the correlation between R/C and the price was directly proportional. There are two types of marketing channels. Channel I, the farmer would directly sell to the tapioca factory with the farmer's share value of 93.31%. Channel II, the farmer would go to the collector, then the collectors would sell to the tapioca factory with a farmer’s share value of 89.92% and the Ratio Profit Margin (RMP) value of 0.49.Key words: cassava, marketing, planting month, price, production